Neonatal pain assessment scales: An integrative review - Jiménez Hernández, Gustavo Edgardo; Bula Romero, Javier Alonso; Sánchez Caraballo, Álvaro Antonio; Peña Zuluaga, Martín Elías (Revista Cuidarte, 2023)
Introduction: Since infants are not able to express their feelings during the preverbal stage of development, neonatal pain rating scales are good tools for nurses to use in clinical practice. Objective: To describe valid and reliable scales used in nursing practice to assess neonatal pain. Materials and Methods: An integrative review of articles published since 1990 was conducted from 2019 to 2020. The databases consulted were PubMed, Lilacs, ProQuest, ScienceDirect, Embase, VHL, Scopus, and Google Scholar metasearch engine. Twenty-two articles that met the inclusion criteria were analyzed. Results: Unidimensional and multidimensional instruments were found for assessing acute and prolonged pain in preterm and term neonates. Discussion: This integrative review provides healthcare professionals, especially nurses, with a conceptual basis for implementing clinical pain assessment tools according to gestational age, duration of pain, and type of indicator. Conclusions: According to the knowledge and characteristics of the scales, it is not possible to clearly establish the most appropriate one for general use or a gold standard; the selection will depend on different criteria, such as the type of stimulus, gestational age, and the newborn’s context.How to cite this article: Jiménez-Hernández Gustavo Edgardo, Bula-Romero Javier Alonso, Sánchez-Caraballo Álvaro Antonio, Peña-Zuluaga Martín Elías. Escalas para valoración del dolor neonatal: Una revisión integrativa. Revista Cuidarte. 2023;14(2):e2760. . http://dx.doi.org/10.15649/cuidarte.2760
Keywords: Scales; Pain Measurement; Newborn